أثر التنظيمات العثمانية على تجارة متسلمية بيروت خلال الحكم المصري لبلاد الشام - العربيات, غالب; النواصره, قاسم (جامعة الوادي - University of Eloued, 2020)
الملخص يهدف هذا البحث إلى إلقاء الضوء على أثر التنظيمات العثمانية على التجارة في متسلمية بيروت خلال الحكم المصري لبلاد الشام (1831–1841م)، ويقدّم البحث أول إشارة من خلال الوثائق إلى أثر التنظيمات في متسلمية بيروت. حيث أصبحت تجارة هذا الميناء ذات نشاط ملحوظ في أعقاب التوقيع على المعاهدات التجارية مع الدول الأوروبية عام 1838م وما تلاها. ويبدو من خلال الوثائق أن النشاط التجاري الأوروبي في متسلمية بيروت قد ظهر جلياً في أعقاب إعلان التنظيمات (1839)، التي أعقبها إنشاء المحاكم التجارية عام 1840م، وذلك من أجل إنهاء الخلافات التي تنشب بين التجار، وبخاصة في مجال التجارة البحرية. . Abstract: The research paper aims to investigate the effect of ottoman regulations on trade in Beirut district under the Egyptian rule of the Levant (1831-1841). The paper provides evidence that such regulations has an important role in this trade. Beirut port had become a key hub of trade especially after several treaties and agreements were signed with several European countries in 1838 onwards. Due to the relevant scripts, the European trading activities become evident due to the announcements of these regulations(1839), which is followed by the establishment of trading courts in 1840. Problems and conflicts between trades were eliminated, particularly when it cone to the navy trading.
1831-1841 ميلادي
مقال
Keywords: التنظيمات العثمانية ; متسلمية بيروت ; الدول الأوروبية ; الحكم المصري ; الدولة العثمانية; Ottoman regulations; Beirut district; European countries; the Egyptian ruling; Ottoman country